DRIVING THE PROPENSITY FOR GREEN ENTREPRENEURSHIP - Kartika Nuringsih; Nuryasman MN; Harry Kristanto (International Journal of Application on Economics and Business, 2026)
The study explores the effect of environmental attitude and environmental education on shaping environmental citizenship behavior (ECB) and the impact of these behaviors on the propensity for green entrepreneurship (PGEN) with respondents at Kulon Progo Region in Daerah Istimewa Yogyakarta province. Under the Adiwiyata school program, the study focuses on environmental education, so it is more suitable to be carried out with schools that commit to environmental conservation. Involving senior high school students with resulting as follows: ECB effects significantly positively on the PGEN. Environmental attitude impacts positively on ECB and PGEN. Environmental education shows a significant effect on ECB, however, giving negative insignificance on the PGEN. The ECB forms partial mediation in linking the relationship between environmental attitude and PGEN. This program can be directed to encourage intention students in green entrepreneurship. Understanding this result, green entrepreneurship is a pathway in introducing education about environmental conservation while learning business.